Genotypic Diversity and Epidemiology of Human Rhinovirus Among Children With Severe Acute Respiratory Tract Infection in Shanghai, 2013–2015 - Zhao, Yanjie; Shen, Jun; Wu, Bingjie; Liu, Gaoshan; Lu, Roujian; Tan, Wenjie (Frontiers in Microbiology, 2018)
Human rhinovirus (HRV), and particularly HRV-C, is increasingly recognized as a cause of severe acute respiratory infections (SARIs). However, little is known about the genotypic diversity and epidemiology of HRV among children with SARI. Thus, we investigated the genotypic diversity and epidemiology of HRV in children with SARI in China over a 2-year period. In total 1,003, nasopharyngeal aspirates were collected from children hospitalized with SARI in Shanghai from 2013 to 2015. HRV was screened for by a PCR method targeting the viral 5′ UTR and was genotyped by sequencing of the VP4–VP2 region of the HRV genome. We also screened for 15 other common respiratory viruses to assess the prevalence of co-infection with HRV. The patient demographic and clinical data were reviewed. HRV was detected in 280 (27.9%) of the 1,003 specimens: HRV-A in 140 (14.0%), HRV-B in 21 (2.1%), HRV-C in 56 (5.6%), and HRV-untyped in 63 (6.3%). A phylogenetic analysis identified 77 genotypes (43 HRV-A, 10 HRV-B, and 24 HRV-C), among which A78, A12, A89, B70, C2, C6, and C24 predominated. HRV-A was detected mainly in winter 2013 and autumn 2014, while HRV-C detection peaked in autumn 2013 and 2014. The detection frequency of HRV-A was highest in patients <5 years old. Most HRV co-infections involved adenovirus, human bocavirus, and/or human respiratory syncytial virus. In conclusion, HRV-A and -C predominate in children with SARI in Shanghai. Among the 77 genotypes detected, A78, A12, A89, B70, C2, C6, and C24 were the most frequent. The HRV species responsible for SARIs differs according to season and age.